1997
DOI: 10.1161/01.cir.96.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Redifferentiation of Smooth Muscle Cells After Coronary Angioplasty Determined via Myosin Heavy Chain Expression

Abstract: Neointimal SMCs show features of an undifferentiated state, indicated by altered expression of SM MHC, and undergo redifferentiation in a time-dependent manner. The expression of SM MHC isoforms provides insight into the biology of healing after angioplasty and furnishes useful tools for the understanding of the roles of differentiation and phenotypic modulation of SMCs in human vascular lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
97
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 48 publications
13
97
0
4
Order By: Relevance
“…The present study is the first to show the suppressive effects of GLP-1 and GLP-1R agonists on PDGF-BB-induced proliferation and migration of human aortic VSMCs. The present study also showed that GLP-1 suppressed SMemb-positive VSMCs, a proliferative phenotype that acquires macrophage-like phagocytosis 20 . In previous studies we showed that chronic infusion of GLP-1 significantly prevented the infiltration of reported that exendin-4 suppresses murine VSMC proliferation and reduces intimal thickening after vascular injury 9 .…”
Section: Discussionsupporting
confidence: 76%
“…The present study is the first to show the suppressive effects of GLP-1 and GLP-1R agonists on PDGF-BB-induced proliferation and migration of human aortic VSMCs. The present study also showed that GLP-1 suppressed SMemb-positive VSMCs, a proliferative phenotype that acquires macrophage-like phagocytosis 20 . In previous studies we showed that chronic infusion of GLP-1 significantly prevented the infiltration of reported that exendin-4 suppresses murine VSMC proliferation and reduces intimal thickening after vascular injury 9 .…”
Section: Discussionsupporting
confidence: 76%
“…We also detected USF binding activity to this E-box in nuclear extracts prepared from intact rat SM tissues. 2 Previous studies in our laboratory provided evidence for a role of USF in SM ␣-actin expression through E-boxes in the 5Ј-flanking sequences (27). Importantly, these E-boxes were required for transcription in vivo in transgenic mice (28).…”
Section: Expression Of the Sm-mhc Gene Is Regulated By Multiple Modulmentioning
confidence: 87%
“…Its expression is regulated precisely and dynamically during SMC differentiation and also during the formation and development of vascular diseases such as atherosclerosis (2,3). Therefore, studies on the mechanisms that regulate SM-MHC gene expression would be of great importance not only for understanding of transcriptional regulatory mechanisms in SMC differentiation but also for the understanding of the mechanisms of phenotypic modulation of SMCs in vascular diseases.…”
mentioning
confidence: 99%
“…Aikawa and colleagues (4,5) found evidence for altered expression of SM MHC isoforms (SM-1 an SM-2) and SM ␣-actin in tissue samples obtained from autopsied patients and atherectomy specimens from patients undergoing percutaneous transluminal coronary angioplasty (PTCA). Medial SMCs were positive for SM-1, SM-2, and SM ␣-actin.…”
Section: B Characterization Of the Smc Within Atherosclerotic Lesionmentioning
confidence: 99%
“…Intimal SMCs have been shown to undergo many additional changes including 1) increased DNA synthesis and expression of proliferation markers and cyclins such as proliferating cell nuclear antigen (PCNA) (77); 2) decreased expression of proteins characteristic of differentiated SMCs including SM MHCs (SM-1, SM-2), SM ␣-actin, SM22␣, smoothelin, h-caldesmin, desmin, calponin, and vinculin and increased ACLP and SMemb (4,129,130,138,183,257); 3) alterations in calcium handling and contractility (49,101,262); and 4) alterations in cell ultrastructure, including a general loss of myofilaments, which is replaced largely by synthetic organelles such as Golgi and rough endoplasmic reticulum, rounding of the cell from its typical elongated contractile morphology, and alterations in basement membrane (129,130,183). The preceding studies have been extended by Geary et al (72), who completed microarray-based profiling of gene expression patterns of SMCs in the neointima formed 4 wk after aortic grafting compared with those from the normal aorta in primates.…”
Section: B Characterization Of the Smc Within Atherosclerotic Lesionmentioning
confidence: 99%